A KAJIAN INTENSITAS CAHAYA DI BAWAH POHON SONO KELING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PORANG (Amorphophallus muelleri Blume): KAJIAN INTENSITAS CAHAYA DI BAWAH POHON SONO KELING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PORANG (Amorphophallus muelleri Blume) - supriyono Supriyono; Nur Fadli Lutfi Hakim; Sri Nyoto; Aprlia Ike Nurmalasari (Innofarm:Jurnal Inovasi Pertanian, 2022)
Porang (Amorphophallus muelleri Blume) is a plant that produces tubers and is widely found in various parts of Indonesia such as Central Java, East Java and East Nusa Tenggara. Porang is used to make glue, food and cosmetics. The high demand for porang requires intensification and expansion of the area to be carried out. The target of land expansion is marginal land, as well as intercropping on forest land or by agroforestry. Appropriate light intensity can increase plant growth and yield. The research was carried out from March to July 2020 in the Perum Perhutani BKPH Pojok, in sonokeling(Dalbergia latifolia) forest, Kemadoh Batur Village, Tawangharjo in Grobogan district. This one factor study used a Randomized Completely Block Design (RCBD) with 4 levels. The treatment factors were light intensity due to shade by sonokeling : (P1) 100% light intensity, (P2) 75-90% light intensity, (P3) 50-74% shading intensity, and (P4) 25-49% light intensity. Each treatment was repeated 6 times, each experimental unit consisted of 3 plants. Data were analyzed using 5% variance test and continued with 5% DMR test if there was a significant difference. Up to 25-49% the light intensity of the  sonokeling shade does not affect the growth and yield of porang plants.